2016
DOI: 10.1021/acs.joc.6b01966
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)-Catalyzed C–H Bond Activation/C–C and C–O Bond Formation Reaction Cascade: Direct Synthesis of Coumestans

Abstract: A palladium catalyzed cascade reaction of 4-hydroxycoumarins and in situ generated arynes has been developed for the direct synthesis of coumestans. This cascade strategy proceeds via C-H bond activation/C-O and C-C bond formations in a single reaction vessel. This methodology affords moderate to good yields of coumestans and is tolerant of a variety of functional groups including halide. The methodology was applied to the synthesis of natural product flemichapparin C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…A promising approach to construct these structures is the oxidative coupling between the catechols and hydroxycoumarins . This reaction has two advantages over other reactions that use halogen‐, trifluoromethanesulfonate‐ or tributyltin‐substituted aromatic compounds as the starting material. This method allows the direct use of substrates without prefunctionalization and involves the formation of C−C and C−O bonds in a cascade‐type reaction.…”
Section: Figurementioning
confidence: 99%
“…A promising approach to construct these structures is the oxidative coupling between the catechols and hydroxycoumarins . This reaction has two advantages over other reactions that use halogen‐, trifluoromethanesulfonate‐ or tributyltin‐substituted aromatic compounds as the starting material. This method allows the direct use of substrates without prefunctionalization and involves the formation of C−C and C−O bonds in a cascade‐type reaction.…”
Section: Figurementioning
confidence: 99%
“…Gogoi and co‐workers reported the direct synthesis of coumestans via a palladium‐catalysed C–H activation/C–C and C–O bond formation cascade invoking aryne chemistry (Scheme ) . Flemichapparin C was also synthesised using this methodology.…”
Section: C–h Activation Of 2‐coumarinsmentioning
confidence: 99%
“…In 2016, Gogoi et al reported the synthesiso fc oumestans 447 from 4-hydroxycoumarins 446 and benzyne precursors 223 (Scheme 129). [185] Thea uthors propose C(sp 2 )-H activation assisted by the coordina- tion of Pd(II) to the alcohol for the formation of coumaroyl-Pd(II) complex 448.I nsertiono ft he benzyne formsintermediate 449 andaBuchwald-Hartwig-type etherification forms the product.B road variation of the R 1 substitution is tolerated, providing the coumestans in good yields.N or egioselectivity was obtained when the benzyne was unsymmetrically substituted.…”
Section: C-h Activationmentioning
confidence: 99%